A fraction containing kaempferol-3,4′-dimethylether from Larrea divaricata Cav. induces macrophage activation on mice infected with Candida albicans - Martino, Renzo Fabricio (2014)
Larrea divaricata Cav. is a plant growing in South America. Both the infusion and a derived fraction (F1) of L. divaricata have proved to have immunomodulatory properties. Moreover, F1 can activate macrophages obtained from mice infected with Candida albicans. In this work, F1 was administrated to infected animals, and the state and type of activation of resident macrophages were studied. Results showed that F1 was able to activate macrophages obtained from infected mice by both classical and alternative pathways, probably by inducing a translocation of nuclear factor kappa-B. F1 increases not only the lysosomal activity of macrophages but also the production of phagosomal superoxide anion as a consequence of the activation of the Nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase) complex. F1 induced an increase in the macrophage capacity to kill the fungus, which was reflected in a decrease in the levels of colonization of organs. A main flavonoid, kaempferol-3,4′-dimethylether, was identified in F1 by HPLC. This compound increased in vitro production of nitric oxide in heat-killed C. albicans-stimulated macrophages. The flavonoid could thus be considered one of the responsible molecules mediating the overall effects of F1 on the immune system in infected animals.